2015
DOI: 10.1371/journal.pone.0122356
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Phosphorylation and SHAGGY-Like Protein Kinases in Geminivirus C4 Protein Induced Hyperplasia

Abstract: Even though plant cells are highly plastic, plants only develop hyperplasia under very specific abiotic and biotic stresses, such as when exposed to pathogens like Beet curly top virus (BCTV). The C4 protein of BCTV is sufficient to induce hyperplasia and alter Arabidopsis development. It was previously shown that C4 interacts with two Arabidopsis Shaggy-like protein kinases, AtSK21 and 23, which are negative regulators of brassinosteroid (BR) hormone signaling. Here we show that the C4 protein interacts with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
59
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 62 publications
2
59
0
Order By: Relevance
“…Previous studies have predicted that the C4 proteins of several geminiviruses could be modified with a myristoyl lipid anchor (14-carbon saturated fatty alkyl chain) on the N-terminal glycine residue, and that myristoylation is essential for the induction of symptoms (Fondong et al, 2007;Piroux et al, 2007;Dogra et al, 2009;Mills-Lujan and Deom, 2010;Mills-Lujan et al, 2015;Hipp et al, 2016;Rosas-Diaz et al, 2018). Additionally, Mills-Lujan et al (2015) reported that phosphorylation of BCTV C4 by AtSKh/BIN2 was important for symptom development. Hipp et al (2016) detected phosphorylation and myristoylation of AC4 from African cassava mosaic virus in yeast using mass spectrometry.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have predicted that the C4 proteins of several geminiviruses could be modified with a myristoyl lipid anchor (14-carbon saturated fatty alkyl chain) on the N-terminal glycine residue, and that myristoylation is essential for the induction of symptoms (Fondong et al, 2007;Piroux et al, 2007;Dogra et al, 2009;Mills-Lujan and Deom, 2010;Mills-Lujan et al, 2015;Hipp et al, 2016;Rosas-Diaz et al, 2018). Additionally, Mills-Lujan et al (2015) reported that phosphorylation of BCTV C4 by AtSKh/BIN2 was important for symptom development. Hipp et al (2016) detected phosphorylation and myristoylation of AC4 from African cassava mosaic virus in yeast using mass spectrometry.…”
Section: Discussionmentioning
confidence: 99%
“…Global transcriptomic changes upon monopartite TYLCSV infection in tomato showed the up-regulation of genes involved in phytohormone metabolism, nucleic acid metabolism and ubiquitin-autophagy pathway, whereas the down-regulated genes were involved in primary metabolism, methylation-dependent chromatin silencing [ 123 ]. Interactions of curtovirus derived C4 and Arabidopsis thaliana SHAGGY-like protein kinases (AtSKs) were implicated in hyperplasia observed during BCTV infection [ 124 ].…”
Section: Geminiviruses and Host Cellular Reprogrammingmentioning
confidence: 99%
“…One of the functional characteristics of C4/AC4 is its induction of hyperplasia and tumorigenic growth in infected plant tissues (Mills-Lujan et al, 2015). This property is consistent with the fact that viruses commonly manipulate the cell cycle to create cellular conditions favorable for viral genome replication by encoding proteins that target host cell cycle regulators.…”
mentioning
confidence: 54%
“…Another key function of C4/AC4 related to cell cycle regulation is the induction of characteristic viral symptoms. For instance, East African cassava mosaic Cameroon virus (EACMCV) was shown to cause crinkling symptoms (Fondong et al, 2007) and Beet curly top virus (BCTV) C4 causes hyperplasia symptoms similar to symptoms observed during a BCTV infection (Mills-Lujan et al, 2015). This is presumed to be a consequence of C4/AC4 interaction with CLAVATA 1 (CLV1) receptor kinase that functions in meristem maintenance .…”
mentioning
confidence: 99%